Behavioral and social science research to support accelerated and equitable implementation of long-acting preexposure prophylaxis. Issue 1 (January 2020) - Meyers, Kathrine; Price, Devon; Golub, Sarit
Abstract : Purpose of review: The sociobehavioral research agenda for HIV prevention urgently needs to progress beyond research on end user preferences to examine how to best support patient access, engagement, and choice in the rollout of long-acting modalities. We outline critical challenges for an era of choice in biomedical prevention that could benefit from the rigorous application of sociobehavioral research methods. Recent findings: Research in three areas could accelerate implementation of long-acting antiretrovirals for prevention: integrating dual process models into research on patient decision-making and behavior; identifying strategies that mitigate against unconscious and implicit biases in provider decision-making and behavior; and developing tools to support patient-centered communication that incorporate research in both of the first two areas. Summary: We encourage the development of dual process models and measures to better understand patient behavior, including behavior related to initiating biomedical prevention, choice of prevention strategy, switching among strategies, and discontinuation. Second, there is the need to develop intervention research that targets provider behavior. Finally, we call for research to inform patient-centered communication tools that integrate an understanding of affective drivers of preexposure prophylaxis (PrEP) decision-making and protect against implicit bias in provider recommendations related to PrEP.